The medicine wheel : environmental decision-making process of Indigenous peoples - Marchand, Michael E.; Vogt, Kristiina A.; Cawston, Rodney; Tovey, John D.; McCoy, John; Maryboy, Nancy; Mukumoto, Calvin T.; Vogt, Daniel J.; Mobley, Melody Starya (Higher Education Press Limited Company ; Michigan State University Press, 2020)
"The goal of this book is to lay the context for how to connect Western science and Indigenous knowledge frameworks to form a holistic and ethical decision-making process for the environment"--